2019
DOI: 10.1002/pd.5588
|View full text |Cite
|
Sign up to set email alerts
|

It takes two: uptake of carrier screening among male reproductive partners

Abstract: Objective To describe uptake of carrier screening by male reproductive partners of prenatal and preconception patients. Methods A retrospective database review of all prenatal and preconception patients seen for genetic counseling in Maternal Fetal Medicine clinics was performed. Descriptive statistics and chi‐square analysis were used on the data set. Results Within the study period, 6087 patients were seen for genetic counseling, of whom 661 were identified as a carrier of an autosomal recessive disorder by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 21 publications
4
68
0
Order By: Relevance
“…In the traditional screening workflow, two separate tests must be ordered, drawn, and reported, resulting in a period of 6-8 weeks to identify high risk fetuses, as demonstrated in a recent study where the average time between maternal result disclosure and paternal blood draw was 13.9 days (Figure 1). 5 Early identification of high-risk fetuses offers clinicians and patients additional time to discuss options for prenatal and neonatal interventions, such as termination of pregnancy. For the model inputs, we used previously reported termination rates (14-55%) for the disorders screened (Table S6).…”
Section: Assumptions For Treatment Cost Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…In the traditional screening workflow, two separate tests must be ordered, drawn, and reported, resulting in a period of 6-8 weeks to identify high risk fetuses, as demonstrated in a recent study where the average time between maternal result disclosure and paternal blood draw was 13.9 days (Figure 1). 5 Early identification of high-risk fetuses offers clinicians and patients additional time to discuss options for prenatal and neonatal interventions, such as termination of pregnancy. For the model inputs, we used previously reported termination rates (14-55%) for the disorders screened (Table S6).…”
Section: Assumptions For Treatment Cost Comparisonmentioning
confidence: 99%
“…A study in 2019 found that 436 out of 462 patients (94.4%) undergoing carrier screening were screened prenatally. 5 The primary goal of carrier screen, when performed prenatally, is to identify high-risk fetuses. First, pregnant mothers are screened for their carrier status.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 In one study, only 38% of male partners followed-up with screening. 7 Lack of male partner follow-up diminishes the ability of ECS to provide clinically actionable results, underscoring the need for mechanisms to efficiently gather the male partner's sample and decrease provider workload.…”
Section: Introductionmentioning
confidence: 98%
“…However, it results in needless testing of partner samples for which no reproductive risk was identified in the other partner. 7 "Tandem reflex" screening is a novel strategy to limit unnecessary partner testing by collecting both partners' samples in tandem, but testing the second partner's sample only if the first partner was found to be a carrier of an autosomal recessive condition (Figure 1).…”
Section: Introductionmentioning
confidence: 99%